Thrombin and Plasmin Alter the Proteome of Neutrophil Extracellular Traps - Lim, Chun Hwee; Adav, Sunil S.; Sze, Siu Kwan; Choong, Yeu Khai; Saravanan, Rathi; Schmidtchen, Artur (Frontiers in Immunology, 2018)
Neutrophil extracellular traps (NETs) consist of a decondensed DNA scaffold decorated with neutrophil-derived proteins. The proteome of NETs, or “NETome”, has been largely elucidated in vitro. However, components such as plasma and extracellular matrix proteins may affect the NETome under physiological conditions. Here, using a reductionistic approach, we explored the effects of two proteases active during injury and wounding, human thrombin and plasmin, on the NETome. Using high-resolution mass spectrometry, we identified a total of 164 proteins, including those previously not described in NETs. The serine proteases, particularly thrombin, were also found to interact with DNA and bound to NETs in vitro. Among the most abundant proteins were those identified previously, including histones, neutrophil elastase and antimicrobial proteins. We observed reduced histone (H2B, H3 and H4) and neutrophil elastase levels upon the addition of the two proteases. Analyses of NET-derived tryptic peptides identified subtle changes upon protease treatments. Our results provide evidence that exogenous proteases, present during wounding and inflammation, influence the NETome. Taken together, regulation of NETs and their proteins under different physiological conditions may affect their roles in infection, inflammation, and the host response.